Students’ Motivation on Speaking Skill at the X Grade of Vocational High School 1 Jambi City - Maya Raudya Haya; Nurul Fitri; Siti Aisyah (Universitas Batanghari Jambi, 2022)
The purpose of this study was to find out what is the motivation of students in terms of speaking skills in class X SMKN 1 Jambi City. This study uses quantitative methods and data collection is done by distributing questionnaires to students. The subjects of this study were 31 students of class X SMKN 1 Jambi City. The results of this study indicate that there are two student motivations in speaking skills, namely intrinsic motivation, namely motivation to be active or not need to be stimulated from outside because everyone has the urge to do something and extrinsic motivation, namely motivation that is motivational. lively and functional. with external stimuli. Thus, from the results of observations and questionnaires, this research concluded that students' speaking skills were caused by intrinsic motivation and extrinsic motivation.